HUBUNGAN PERAN ORANG TUA TERHADAP HASIL BELAJAR SISWA KELAS 3 PADA MATA PELAJARAN MATEMATIKA DI SDIT AL IRSYAD AL ISLAMIYAH DAWUHAN KECAMATAN SITUBONDO - Akbar, Saiful; Efendi, Dodik (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2023)
Role of parents and the learning outcomes of grade 3 students in the mathematics subject at SDIT Al Irsyad Al Islamiyah Dawuhan, Situbondo District. The purpose of this study was to explain the relationship between the role of parents and the learning outcomes of grade 3 students in Mathematics at SDIT Al Irsyad Al Islamiyah Dawuhan, Situbondo District. This research method is a type of quantitative descriptive research by drawing conclusions through statistical analysis. The population in this study were all 3rd grade students at SDIT Al Irsyad Al Islamiyah Dawuhan. Samples were taken as many as 16 students with random sampling technique. The necessary data is obtained through questionnaires and data on student learning outcomes. The data analysis technique used is product moment analysis. After conducting research and obtaining data, then analyzing the data from the questionnaire results and student learning outcomes, an rcount of 0.932 was obtained, while an rtable of 0.532 at N = 16 with a significant level of 5% means that rcount > rtable means that Ho is rejected and Ha is accepted. So it can be concluded that there is a significant relationship between the role of parents and the learning outcomes of grade 3 students in the mathematics subject of SDIT Al Irsyad Al Islamiyah Dawuhan, Situbondo District.